ANALISIS EFEKTIFITAS DAN KONTRIBUSI PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) TERHADAP PENDAPATAN DAERAH DI KABUPATEN GRESIK - ADELINA, RIMA (Jurnal Akuntansi AKUNESA, 2013)
Land and building tax revenues as a source of potential revenue and if the collectiondone efficiently and effectively, its full potential can be tapped by both as well as contributingto regional income. Determine of this study is to the magnitude of effectiveness of land andbuilding tax receipts and contribution receipts tax on income from land and building area inGresik District. Analysis of methods study was conducted by using qualitative descriptivemethod to describe the effectiveness of land and building tax receipts as well as contributeland and building tax receipts for local revenue in Gresik District in 2007 to 2011. From theanalysis of discussion can be seen that the collection of land and building tax in GresikDistrict has shown figures that are very effective with the average 104,28%. Then,contribution for land and building tax to local revenue in Gresik District somewhat lackingwith average 5,43%, so the land and building tax contribution can’t be perceived by GresikDistrict community.Keywords: Local revenue, Land and Building Tax, Effectivity, Contribution